In vivo production of interferon β by human Tenon's fibroblasts; a possible mediator for the development of chronic conjunctival inflammation. Issue 6 (1st June 2002) - Chang, L; Siriwardena, D; Wilkins, M R; Crowston, J G; Akbar, A N; Khaw, P T
Abstract : Background: Chronic inflammation may develop from failure of the immune system to deactivate itself during resolution of the wound healing response, and is recognised as a major risk factor for trabeculectomy failure. Fibroblast/T cell interactions may contribute to aggressive scarring. Our previous research showed that in vitro human Tenon's fibroblast produced interferon β was responsible for preventing T cell apoptosis, suggesting that this interaction could contribute to the development of chronic inflammation. Methods: Immunohistological techniques were used to investigate the in vivo components of this particular fibroblast/T cell interaction in conjunctival biopsies from glaucoma patients undergoing filtration surgery. Results: Fibroblast produced interferon β and T lymphocytes were identified in human conjunctiva. Conclusion: The components of fibroblast mediated prevention of T cell apoptosis were identified in vivo, suggesting that the development of this interaction is possible and that it may contribute to the development of chronic inflammation and excessive scarring.